Investigating the interplay between Wilms’ Tumour Protein 1 and oxidised forms of 5-Methylcytosine in brain tumours - Ramsawhook, Ashley (2020)
5-methylcytosine (5mC) is an epigenetic modification usually associated with transcriptional repression. The Ten–Eleven Translocation proteins (Tet1/2/3) can oxidise 5mC to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC) in vertebrate DNA. These modifications have not been well characterised but have been detected during embryogenesis, in somatic adult healthy and malignant tissues. Transcription factor and tumour suppressor/ oncogene Wilm’s Tumour protein 1 (WT1), though not expressed in healthy brains displays over-expression in high grade neoplasms including Glioblastoma multiforme (GBM) and has been associated with poor patient prognosis. Interestingly, WT1 possesses preferential binding affinity for 5mC and 5caC over unmodified cytosines, 5hmC and 5fC in vitro. Thus we speculate that a WT1-5caC relationship may exist within a DNA demethylation associated and possible a transcriptional regulatory context in brain tumours. Utilising a range of techniques including genome editing and Next Generation Sequencing, we demonstrate that 5caC is enriched in brain tumour cell lines, is depleted upon WT1 mutagenesis and may share genomic occupancy on gene regulatory and intragenic sequences. Additionally, we demonstrate a compromised neurosphere formation phenotype evident in WT1 zinc finger mutant GBM cell lines which correlates with perturbed extracellular matrix and cell adhesion gene expression, and is correlated with reduced tumour formation in vivo.